2008
DOI: 10.1080/00288230809510436
|View full text |Cite
|
Sign up to set email alerts
|

Optimal conditions for hydropriming lucerne seeds

Abstract: Poor seedling establishment is a major deterrent in adopting direct seeding of lucerne because of slow and non-uniform germination in pasture establishment. Seed priming to obtain better crop stands could be an attractive approach. The optimal conditions under which to hydroprime lucerne seeds were developed though a series of experiments. This strategy will cut expenses, and make possible the priming of seeds on a large scale without the need to handle the dispose of large quantities of expensive osmotic solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Because the seeds were soaked in water, it is possible that both water and ultrasound were important during the ultrasound treatment. The effect of water on seeds has been reported [32] [34] . Soaking seeds in water before sowing and drying after soaking, which is called hydropriming, is a simple method to enhance seed germination and seedling emergence.…”
Section: Discussionmentioning
confidence: 99%
“…Because the seeds were soaked in water, it is possible that both water and ultrasound were important during the ultrasound treatment. The effect of water on seeds has been reported [32] [34] . Soaking seeds in water before sowing and drying after soaking, which is called hydropriming, is a simple method to enhance seed germination and seedling emergence.…”
Section: Discussionmentioning
confidence: 99%
“…The slight increase in  b (50) in our study may be partially attributed to the relatively high water potential during priming. A further reduction of ambient water potential during hydropriming could be a key issue to improve priming quality (Liu et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al (2008) optimized hydropriming conditions of M. sativa seeds, and they found that hydropriming significantly increased germination rate but not final germination percentage. However, in their study, primed seeds were not re-dried prior to use.…”
Section: Introductionmentioning
confidence: 99%
“…The duration which produces best outcomes of seed priming differs in different crop species/seed type. For example, 18 hours was found optimum for maize 20 , for rice 48 hours was found optimum 26 , in lucerne it was 3-5 days 23 and for cowpea, only 2 hours priming was found enough 24 .…”
Section: Discussionmentioning
confidence: 95%
“…The rate of water absorption rises as anaerobic conditions develop, potentially causing seed damage 22 . For example, hydropriming with water in the range of 90-100 percent of seed weight was shown to be optimum in lucerne seeds and higher amount of water resulted in reduction of seed performance 23 . While, in case of cowpea seeds, a volume twice the seed weight produced better results than a half and equal volume, however, the priming duration was shorter (2 hours) 24 .…”
Section: Discussionmentioning
confidence: 99%